Cross-sectional descriptive observational study of RT PCR proven category C H1N1 patients at tertiary care centre from January 2015- December 2015 - Paritekar, Anita A.; Bansode, Mahendra V.; Waikar, Anushka K.; Borse, Rohidas T. (International Journal of Research in Medical Sciences, 2017)
Background: The onset of winter of 2014-2015 saw an alarming spurt in influenza A (H1N1) pdm 09 leading to a significant mortality. H1N1 primarily affects the very young, elderly, pregnancy and those patients with comorbidities. But the epidemiologic hallmark of pandemic influenza is its "pandemic signature " meaning most early mortalities are among young healthy adults. Methods: To study clinical profile, premorbid conditions and radiological features of Category C H1N1 proven by RTPCR retrospectively from hospital records from Jan 2015 to Dec 2015 at Tertiary Care Centre. Results: Total 108 cases RT PCR proven category C H1N1 studied from hospital records. 43 were males and 65 females. The mean age group was 50 years for males and 40 for females. Common symptoms were fever, cough, dyspnoea with pre-morbid illness like hypertension, diabetes mellitus, pregnancy, cancer and immune compromised with pulmonary tuberculosis. Radiologically there was lower zone involvement common in live patients and reticulonodular was common in death cases. Conclusions: In current study young to middle age group was commonly affected. Pre-morbid conditions, more than two risk factors and late referral were the most common findings in death cases.